Structural Design and Implementation of Simulating Galago Senegalensis Monkey Single-leg Jumping Robots - Li Jing; Li Gui; Sun Wei; Chen Haozuo; Ye Mao; Li Ronghe (Jixie chuandong)
Aiming at the main problems existing in the jumping robot, combined with the galago senegalensis monkey's characteristics of small sizes, stable and explosive jumping, a kind of galago senegalensis monkey single leg jumping robot is proposed in this study, and its main structure and control system are designed. Based on the principle of the Stephenson's six-bar linkage, a planar eight-bar linkage for the leg of simulating galago senegalensis monkey robot is designed, and its trajectory is optimized to obtain the bar length parameters with the best jumping ability. The three directions of the robot's jumping are controlled and adjusted, and the double closed-loop feedback control system is used to ensure the stability of the robot's attitude when taking off, soaring in the air, and landing on the ground. Finally, the physical verification model of the robot is established. The total weight is only 395.5 g, and the overall height is 250 mm. The experimental results show that the simulating single leg robot can achieve continuous and stable jumping, the highest jumping speed can reach 20 m/s, and the response time at a jumping height of 100 mm is 0.1 s.